SiC 복합체 보호막 금속 피복관의 개발 및 고온산화 특성 분석 - 노선호(Seonho Noh); 이동희(Dong-hee Lee); 박광헌(Kwangheon Park) (Biuletyn Uniejowski, 2015)
The goal of this study is to investigate a metal cladding that contains SiC composites as a protective layer and analysis the characteristics of the specimens on high temperature oxidation To make SiC composites, the current process needs a high temperature (about $1100^{°}C$) for the infiltration of fixing materials such as SiC. To improve this situation, we need a low temperature process. In this study, we developed a low temperature process for making SiC composites on the metal layer, and we have made two kinds: cladding with protective SiC composites made by polycarbosilane(PCS), and a PCS filling method using supercritical carbon dioxide. A corrosion test at $1200^{°}C$ in a mixed steam and Ar atmosphere was performed on these specimens. The result show that the cladding with protective SiC composites have excellent oxidation suprression rates. This study can be said to have developed new metal cladding with enhanced durability by using SiC composite as protective films of metal cladding instead of simple coating film.